(untitled) (Research, Society and Development, 2022)
Ashes constitute a waste produced in the heat generation process from bioenergy. This study aimed to improve the biomass energy efficiency used in an industrial boiler. The physicochemical analysis was used to perform improvement in the quality of the biomass for solid fuel. Four biomass types (eucalyptus bark, wood chips, sawdust, and recycled wood waste) were analyzed. The material (ash) was collected every two months over one year. All samples were characterized regarding proximate analysis, chemical composition (macro and micronutrients), morphological characterization (via scanning electron microscopy [SEM] coupled with dispersive energy spectroscopy [EDS]), and particle size distribution. The four biomass types presented significant differences in moisture content and proximate analysis. The bark showed a high percentage of impurities with an ash content of 26.99%. It was possible to reduce the ash content of the biomass inserted into the boiler in half, by separating the bark in the granulometric strata and excluding the smallest particle size (<0.84 mm). The results regarding the ashes showed that chemical composition and physical attributes were similar in all samples over the year. The chemical components were the same, although they varied in quantity. It is possible to improve the biomass energetic performance by excluding the smallest particles prior to the boiler insertion.